Total Thickness Bilateral Rupture of the Rectus Abdominis: A Case Report and Literature Review - Dernas Suhail; Olivia Smith; Philip Lim; Srinivas Chintapatla (Case Reports in Surgery)
Rupture of the rectus abdominis is a rare condition. We describe the case of a young male trainee paratrooper who presented with sudden onset severe lower abdominal pain that occurred during military training. Magnetic resonance imaging revealed full-thickness bilateral rupture of the rectus abdominis. Our management involved injecting botulinum toxin into the rectus muscles preoperatively, reconstructing the rectus muscles, and placing a supportive biosynthetic mesh. Postoperatively, our patient could walk pain-free at 3 weeks, jog pain-free at 10 weeks, and run up to 2 miles at 25 weeks. As there is no consensus on the management of this rare injury, we conducted a literature review on all cases reporting rupture of the rectus abdominis from the year 2000. After comparing the outcomes of conservatively versus surgically managed patients, we can conclude that generally, management of such defects is dependent on size, severity, and patient factors; however, surgical treatment yields comparable results to conservative treatment.